Gambaran Pengetahuan dan Sikap Remaja Putri terhadap Personal Higiene saat Menstruasi di SMP N 19 Kota Jambi Tahun 2018 - Liza Liza (Jurnal Akademika Baiturrahim Jambi, 2019)
Health care and hygiene are things that are widely discussed in the community. For teenagers this is considered not important because they do not know the impact that will be caused if this is not done properly, especially during menstruation. While during menstruation issued not only blood cells but also epithelial cells of the uterine wall. In the world, the incidence of reproductive infections is around 2.3 million per year, mostly teenagers. According to the percentage of schools with the third highest number of students found in SMP N 19 Jambi City, with a target number of VIII grade students of 138 students. This study aims to determine the description of knowledge and attitudes of young women towards personal hygiene during menstruation at SMP N 19 Jambi City in 2018. The population in this study was VIII grade students totaling 138 female students. The number of samples is 58 students taken randomly using simple random sampling technique. This study uses univariate analysis to describe the frequency distribution table of the studied variables. The results of data analysis showed that respondents who had poor knowledge were 38 respondents (65.5%), and respondents with negative attitudes were 32 respondents (55.2%). It is hoped that in future schools will pay more attention to the knowledge of students about adolescent reproductive health by providing reading books and occasionally working with the nearest health center to conduct counseling.